Securing Internet of Things(IoT) Using HoneyPots - Sudha Gadde, Sai; Krishna Srinivas Ganta, Rama; Gopala Gupta, ASALG; Rao K, Raghava; Mohan Rao, KRR (International Journal of Engineering and Technology, 2018)
In todayâ€™s everlasting technological world, information and data communication create more devices stay connected to the internet. This lead to achieving development for building different software and internet connection very inexpensive this affected privacy and security. Security today became of the most important issue because day-by-day new technologies are put forward for different purposes of study while these come with a lot of vulnerabilities which makes the exploitation of the data. IoT is also such kind technology which is available for exploiting. For preserving information from such type of attacks we use honeypot which serves as a decoy based technology in a network and these are cost effective and works as a deception model which entice attackers with low vulnerabilities and security. Here are how honeypots used to defend IoT devices from being attacked and gather information about the attackersâ€™ device.Â